Pengaruh Fasilitas Dan Harga Terhadap Kepuasan Berkunjung Wisatawan Di Obyek Wisata Pulau Pahawang (Studi Kasus PT. Aero Travelindo Utama) - Setiawan, Benny; Yusda, Desi Derina; Indriyani, Susi (Universitas Mitra Indonesia, 2024)
This study aims to determine and test whether the variables of facilities and prices have an effect on tourist satisfaction at the Pahawang Island Tourism Object. The data collection technique was carried out by giving questionnaires to visitors, in sampling using the Slovin formula by obtaining a sample of 98 respondents. In this study, through partial testing, it can be seen that the facility variable does not have a positive and significant effect on tourist satisfaction, while the price variable has a positive and significant effect on tourist satisfaction at the Pahawang Island Tourism Object (case study of PT. Aero Travelindo Utama). Keywords : Facilities, Prices, Tourist Satisfaction